Two‐Dimensional GaX/SnS2 (X = S, Se) van der Waals Heterostructures for Photovoltaic Application: Heteroatom Doping Strategy to Boost Power Conversion Efficiency. Issue 5 (2nd January 2019) - Wu, Hong‐Yu; Yang, Ke; Si, Yuan; Huang, Wei‐Qing; Hu, Wangyu; Huang, Gui‐Fang
Abstract : Two‐dimensional (2D) heterostructures with novel and tunable physical properties are regarded as promising candidates for high‐efficiency photovoltaics. The band gap and band alignment at the interface are fundamental properties determining photovoltaic‐device efficiency. Here, by systematic first‐principles density‐functional calculations, we demonstrate that 2D GaX/SnS2 ( X  = S, Se) van der Waals heterostructures with a narrow band gap are solar cell candidate materials. The results show that compared to their individuals, the band gaps of the heterostructures are significantly reduced, allowing harvesting a wide range of solar light. The type‐II band alignment at the interface would promote the electron transfer from one constituent to another, and enhance the separation efficiency of electron–hole pairs in the heterostructures. Interestingly, heteroatom doping, especially N atom doping can significantly increase the power conversion efficiency (PCE) of 2D GaX/SnS2 heterostructures up to 16% (increased by 162%). This work suggests that the heteroatom doping strategy is an effective scheme to develop efficient 2D heterostructure‐based optoelectronic devices. Abstract : Two‐dimensional (2D) GaX/SnS2 ( X  = S, Se) heterostructures with tunable band structure and strong optical absorption ability are demonstrated. Heteroatom doping can significantly increase the power conversion efficiency (PCE) of GaX/SnS2 heterostructures up to 16% (PCE without dopants: 6%). The heteroatom doping method paves the way for designing 2D heterostructure‐based high‐efficiency solar energy harvesting candidates.